Epilepsy, electroclinical features, and long‐term outcomes in Pitt–Hopkins syndrome due to pathogenic variants in the TCF4 gene. (7th October 2021) - Matricardi, Sara; Bonanni, Paolo; Iapadre, Giulia; Elia, Maurizio; Cesaroni, Elisabetta; Danieli, Alberto; Negrin, Susanna; Zagaroli, Luca; Operto, Francesca Felicia; Carotenuto, Marco; Pisani, Francesco; Turco, Emanuela Claudia; et al.
Abstract: Background and purpose: Pitt–Hopkins syndrome (PTHS) is a rare neurodevelopmental disorder caused by deletions/variants in the TCF4 gene. Seizures may be present in up to half of the patients, leading to a more severe disease burden. This study aims to analyse the electroclinical phenotype, treatment options, and long‐term outcomes of epilepsy in PTHS. Methods: A multicentre observational cohort study was performed, and the electroclinical data of PTHS individuals affected by epileptic seizures were retrospectively reviewed and analysed. Results: The series includes 21 patients (11 female) with a median age at seizure onset of 2 years (range = 0.5–8). The median time of follow‐up was 7.9 years (range = 2–27). Both generalized and focal epilepsies were present at the same prevalence (42.8%), whereas a minority of patients presented developmental and epileptic encephalopathies (14.4%). At the long‐term follow‐up, 42.8% achieved seizure freedom, whereas 42.8% developed drug‐resistant epilepsy (DRE). The age at seizure onset was found to be an independent predictor for seizure outcome; in this regard, patients having seizure onset after the age of 2 years were more prone to achieve seizure freedom (odds ratio = 0.04, 95% confidence interval = 0.003–0.53; p = 0.01). During evolution, seizures tended to settle down, and even in patients with DRE, seizures tended to persist at a lower frequency and appeared to be more easily manageable over time. Conclusions: This study provides new insight into the natural history of epilepsy in PTHS. Better characterization of epileptic phenotype and prompt tailored treatment improve overall management and quality of life. Abstract : We report on newly diagnosed patients affected by Pitt–Hopkins syndrome (PTHS) and epilepsy with long‐term follow‐up to highlight the natural history of epilepsy in these patients. Epileptic seizures represent a more severe disease burden, and the careful assessment of the epileptic phenotype and prompt tailored treatment may optimize management and quality of life.